Local Cultural Heritage “Omo Hada” As An Icon Of Cultural Tourism Attraction In West Nias District - Kristina Octavia Sitompul; Yustina Denik Risyanti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Cultural heritage is one of the attractions of cultural tourism to attract tourists to visit a place. The local cultural landscape in the form of traditional houses and megalithic remains scattered across West Nias Regency is a special attraction for tourists. War strategies and local traditional rituals influenced the figure of Omo Hada. Buildings characterized by oval-shaped vernacular architecture are called in the local term